Discrimination experiences of transgender individuals in healthcare: an interview study on the perspective of health professionals specializing in the treatment of transgender individuals - Tobias Skuban-Eiseler; Marcin Orzechowski; Florian Steger (BMC, 2024)
Abstract Background Experiences of discrimination in healthcare lead to poorer mental and physical health for transgender individuals. There is evidence that trans-specialists, i.e. health professionals specializing in transgender care, are an important source of discrimination experienced by transgender individuals in healthcare. In this qualitative interview study, we explored the reasons for this possibly surprising finding by analyzing subjective views of trans-specialists on various issues related to discrimination of transgender individuals. Methods We conducted 20 semi-structured, qualitative, exploratory interviews with healthcare professionals specializing in transgender care. Interview questions were developed based on an extensive literature analysis and results of previous research on the topic. The interviews were conducted online, were digitally recorded and transcribed. Data analysis was conducted using the methods of content analysis and thematic analysis. Results The interviewees had great difficulty giving a consistent definition of the concept of gender identity. Most of them saw it as a self-determination of a transgender individual. Although herewith emphasizing the autonomy of transgender individuals, most trans-specialists felt that they had to be convinced of their patient's transsexuality to carry out treatment. Most trans-specialists reported having had doubts about whether some transgender individuals were suffering from gender incongruence or not. There was also ambiguity among interviewees about whether transsexuality is a mental illness. Conclusions We were able to identify specific topics that can cause discrimination experiences on the part of transgender individuals in their contact with trans-specialists. These include the vagueness of the construct of gender identity and the ambivalence between respect for the autonomy of transgender individuals and the validation of the diagnosis "transsexuality". Also, uncertainties regarding the classification of transsexuality as a mental illness can lead to experiences of discrimination. Furthermore, our results imply that trans-specialists might remember own discriminatory behavior less than it actually took place. Our results can contribute to the development of specific measures to avoid discrimination experiences of transgender individuals in contact with trans-specialists. These should include a reflection on one's own gender identity and training on mechanisms of discrimination.